Reengineering management the mandate for new leadership - Champy, James (HarperBusiness, 1995)
Today's management practices hearken back to the early 1900s, when corporations changed from owner leadership to professional managers who began to run companies like controllable, predictable machines. Now that corporations have taken pains to reengineer their operational processes, the management processes must change in accordance. In Reengineering Management, Champy reveals that these processes must focus on mobilizing, enabling, defining, measuring, and communicating in order to achieve a business culture that enables a continuous process of reengineering - in order, in short, to achieve success. For the hundreds of thousands of managers who have read Reengineering the Corporation and the millions who have been touched by the reengineering revolution, Reengineering Management is the book that can deliver the reality behind the promise